2005
DOI: 10.1002/app.21979
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in blends containing chitosan with functionalized polymers

Abstract: ABSTRACT:The phase behavior of blends containing chitosan with poly(vinyl-alcohol) (PVA) and poly(2-hidroxyethyl methacrylate) (P2HEM) was analyzed. Blends were obtained by casting from acetic acid solution (HAc) and 1,1,1,3,3,3 hexafluoro-2-propanol (HF2P) and studied by DSC, FT-IR, and TGA. The phase behavior of the blends of chitosan with PVA and P2HEM, studied by DSC, shows that the systems behave as one-phase systems in HAc as well as in HF2P according to the DSC results. According to the results of FT-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Hong and Choi [28] found a similar profile for a polysaccharide-protein complex isolated from A. blazei fruiting body. A similar behavior has been described for other polysaccharides such as chitosan [30] and galactomannan [31]. Jayakumar et al [32] also reported a slight decrease in the thermostability of chitin after sulfation.…”
Section: Resultssupporting
confidence: 75%
“…Hong and Choi [28] found a similar profile for a polysaccharide-protein complex isolated from A. blazei fruiting body. A similar behavior has been described for other polysaccharides such as chitosan [30] and galactomannan [31]. Jayakumar et al [32] also reported a slight decrease in the thermostability of chitin after sulfation.…”
Section: Resultssupporting
confidence: 75%
“…One of the hot and controversial topics about this system is its compatibility, which is closely relevant to the extent of polymer-polymer interactions. Strong evidences from accurate measurements have shown that this system is not fully miscible at molecular level, depending on the preparation processing and/or the fraction of a certain composition (Castro, Gargallo, Leiva, & Radic, 2005;Jawalkar, Raju, Halligudi, Sairam, & Aminabhavi, 2007;Nakano et al, 2007;Sandoval, Castro, Gargallo, Radic, & Freire, 2005). This special behavior of chitosan/PVA blend arises from the weak interaction between PVA and chitosan as a result of their tight intramolecular structure.…”
Section: Introductionmentioning
confidence: 94%
“…[12,13] One of the hot and also controversial topics about this blend is their miscibility. [14][15][16][17][18][19][20] Strong evidence from some accurate measurements has shown that CS/PVA blend is not fully miscible at molecular level. The miscibility between CS and PVA in the blend was observed to depend on the preparation processing and the relative content of CS and PVA components.…”
Section: Introductionmentioning
confidence: 99%
“…The miscibility between CS and PVA in the blend was observed to depend on the preparation processing and the relative content of CS and PVA components. [11,14,[15][16][17] This special behavior of CS/ PVA blend was partly contributed to the weak intermolecular interaction between PVA and CS because of their tight intramolecular structure. [15] It is well known that the chemical nature of side chains of vinyl polymers usually acts as the main factor in their miscibility behaviors.…”
Section: Introductionmentioning
confidence: 99%